Analisis Perkerasan Lapisan Tambahan pada Jalan Tirto-Joyo Landungsari Indah di Kota Malang - Conceicao Soares , Jose Da ; Arifianto, Andy Kristafi ; Rahma, Pamela Dinar (Prosiding SENTIKUIN (Seminar Nasional Teknologi Industri, Lingkungan dan Infrastruktur), 2018)
Tirto-Joyo Landungsari is a road that connects Dau Subdistrict with Batu District. This road is included in the classification of Local roads (Alternatives), namely roads that are passed by vehicles that are quite large and have a heavy burden. Because frequent heavy-duty vehicles are traversed causing the road to become damaged, the road needs to be repaired or re-rehabilitated. Based on the conditions in the location, the additional layer pavement analysis (overlay) on the beautiful Tirto-Joyo Landungsari road from (sta.0 + 000-sta.0 + 1000) Malang is intended to support the rate of economic growth by increasing the need for transportation facilities that can smooth transportation in the area and the development of the quality and quantity of vehicles that connect Dau Subdistrict with Batu District. In this study, the author will discuss the process of additional layer pavement analysis (overlay) in the Tirto-Joyo Malang road improvement project, as well as explain the methods carried out in an additional layer pavement (overlay). The method used in this study is the Bina Marga Method can be obtained by thick pavement arrangement consisting of a lower base (Sub Base) 18 cm thick with class B aggregate, upper base (Base Course) 20 cm thick with class A aggregate, surface layer (Surface ) 4 cm Laston. This final project report is expected to be useful for the author himself to add knowledge in calculating the thickness of the additional pavement layer (overlay), so that road planning is expected to be able to spur economic growth in the region and in the future the welfare of the community can be lifted.